Polystyrene microplastics impair the function of human retinal microvascular endothelial cells and pericytes and increase vascular permeability in vitro - Yun, Jang-Hyuk (Frontiers in Medicine, 2025)
IntroductionPolystyrene (PS) microplastics are among the most prevalent types of microplastics responsible for global pollution. Although numerous studies have investigated the effects of PS on various organs, such as the heart, lungs, liver, kidneys, nervous system, and intestines, its impact on the eyes, particularly the retina, remains largely unexplored.MethodsTo assess the effects of PS on retinal pathology, cultured retinal microvascular endothelial cells, pericytes, astrocytes, and microglial cells were exposed to 2 μm PS particles. Cell viability (MTT assay), apoptosis (Annexin V/PI flow cytometry), protein expression (Western blotting), and angiogenesis-related behaviors (tube formation, migration, and permeability assays) were evaluated.ResultsPS induced endothelial cell apoptosis by reducing the activity of AKT and ERK1/2, and induced pericyte apoptosis by reducing the activity of AKT. PS also impaired tube formation, migration, and proliferation by reducing AKT and ERK1/2 activity in retinal endothelial cells. In addition, PS induced pericyte apoptosis and increased endothelial permeability.ConclusionPS may worsen retinopathy by inducing endothelial cell and pericyte apoptosis and by increasing vascular leakage, although it does not promote angiogenesis.